Relationship Between Prenatal and Perinatal Factors with the Incidence of Mental Retardation Among Children in Padang City 2017 - Marzatia Yulika; Abdiana Abdiana; Ulvi Mariati (Journal of Midwifery, 2017)
Mental retardation is a condition of intellectual function that is below the average before the age of 18 years. Almost 83 million people around the world are estimated to have mental retardation. With 41 million have long term mental disability. Although the main cause of mental retardation is still fully unknown, prenatal and perinatal factors are suspected to be the risk factors for this. This study aims to determine the relationship between prenatal and perinatal factors with the incidence of mental retardation among children in Padang City.This was an observational analytic study with case control design. Population of this study divided into two, the case population ( all mothers of  mentally retarded child) and control population (all mothers of normal children). The sample was 49 people taken by cluster sampling with the comparison case : control (1:1). Data collected by questionnaire. Data analysis was performed using Chi Square.The result of this study showed that there is a significant relationship between prenatal and perinatal factors such as maternal age (OR=8.4; 95% CI 2.8-24.9; P=<0.001), father’s age (OR=2.4; 95% CI 1.1-5.6; P=<0.043), parity (OR=4.01; 95% CI 1.7-9.4; P=<0.002), asphyxia (OR=23.2; 95% CI 2.9-184.1; P=<0.001) and birth weight (OR=9.3; 95% CI 1.1-78.04; P=<0.031) with the incidence of mental retardation. Factors which does not have a significant relationship in this study are hypertension in pregnancy (P=0.617), prematurity (P=0.111) and type of labor (P=0.132).Parents < 20 years old or ≥35 years old and having parity ≥3 would be more at risk to have mentally retarded child. New born with asphyxia and born weight < 2500 grams are also at risk for mental retardationTherefore it is advisable forpeople to avoid the risk of pregnancy by age and medical attention during pregnancy to avoid the occurrence of low birth weight and asphyxia at birth.